Cross-sex relationships at work and the impact of gender stereotypes - Devine, I. (Journal of business ethics, 1990)
Organizations pride themselves on their creation of rational structures based primarily on a male perspective of interaction. Workers are expected to set aside interpersonal behaviours that do not directly contribute to task performance. As more women enter management, norms concerning appropriate interpersonal relationships at work are undergoing strain. In addition, the phenomenon of mutual sexual attractions between co-workers is demanding attention. This study systematically describes attitudes, attributions and anticipated consequences of mutual sexual attractions at work. Findings suggest that gender stereotypes are significant factors in people's judgments of persons involved in sexual attractions at work.